2017
DOI: 10.1007/s10803-017-3135-z
|View full text |Cite
|
Sign up to set email alerts
|

A Discrepancy in Comprehension and Production in Early Language Development in ASD: Is it Clinically Relevant?

Abstract: This study examined the extent to which a discrepant comprehension-production profile (i.e., relatively more delayed comprehension than production) is characteristic of the early language phenotype in autism spectrum disorders (ASD) and tracked the developmental progression of the profile. Our findings indicated that a discrepant comprehension-production profile distinguished toddlers (30 months) with ASD from late talkers without ASD (91% sensitivity, 100% specificity) in groups that were comparable on expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
(123 reference statements)
3
15
0
Order By: Relevance
“…Given the atypical receptive-expressive vocabulary profile in children with ASD (Davidson & Ellis Weismer, 2017;Hudry et al, 2010;Kover et al, 2013), we suspect that the particular difficulty in the receptive-to-expressive generalization observed in this study reflects a unique difficulty in receptive vocabulary learning or reduced receptive advantage in children with ASD rather than a difference in task demands across expressive and receptive vocabulary learning. Previous studies on the discrepant receptive-expressive vocabulary profile in children with ASD have suggested that children with ASD may demonstrate focused impairments in receptive vocabulary learning because they benefit less from the ambient linguistic input in the environment and may require more supportive contexts to learn new words (McDaniel, Yoder, Woynaroski, & Watson, 2018;Woynaroski et al, 2016).…”
Section: Cross-modal Generalizationmentioning
confidence: 78%
“…Given the atypical receptive-expressive vocabulary profile in children with ASD (Davidson & Ellis Weismer, 2017;Hudry et al, 2010;Kover et al, 2013), we suspect that the particular difficulty in the receptive-to-expressive generalization observed in this study reflects a unique difficulty in receptive vocabulary learning or reduced receptive advantage in children with ASD rather than a difference in task demands across expressive and receptive vocabulary learning. Previous studies on the discrepant receptive-expressive vocabulary profile in children with ASD have suggested that children with ASD may demonstrate focused impairments in receptive vocabulary learning because they benefit less from the ambient linguistic input in the environment and may require more supportive contexts to learn new words (McDaniel, Yoder, Woynaroski, & Watson, 2018;Woynaroski et al, 2016).…”
Section: Cross-modal Generalizationmentioning
confidence: 78%
“…However, the deficit of language comprehension was not homogeneous, since receptive grammar was more impaired than receptive vocabulary. The above language profile differs from the one usually observed in children with a primary developmental language disorder, which is generally characterized by better receptive abilities as opposed to expressive language abilities [16,[44][45][46]. The discrepancy between receptive and expressive skills in children with ASD is, however, still a debated issue, because it is not clear whether it could be considered a specific marker of ASD.…”
Section: Discussionmentioning
confidence: 92%
“…The majority of published studies report that, in ASD, receptive language is more impaired than expressive language [5,11,[16][17][18][19][20][21], but this finding has not been completely confirmed [22,23]. Moreover, the issue of the discrepancy between receptive and expressive competences is still unclear in terms of whether it should be considered as a possible marker of ASD, or whether both receptive and expressive language difficulties are comorbid to ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hudry et al (2010) identified group differences in ASD severity for groups of children with ASD who did versus did not exhibit atypical receptiveexpressive profiles on the MB-CDI, but ASD severity did not predict receptive-expressive difference scores in the Kover et al (2013) sample. Mixed results are also evident for chronological age (Davidson & Ellis Weismer, 2017;Haebig & Sterling, 2017;Hudry et al, 2010;Kover et al, 2013;Kwok et al, 2015). None of these predictors are clearly malleable in children with ASD.…”
Section: Previously Investigated Predictors Of Receptive-expressive Dmentioning
confidence: 98%
“…n contrast to delayed language development, which follows the typical course but at a slower rate, deviant language development is characterized by patterns of skills not observed in typical development (Kamhi, 1998;Loeb & Leonard, 1991). An atypical discrepancy between receptive and expressive language skills exhibited by some children with autism spectrum disorder (ASD) is one manifestation of deviant language development (e.g., Davidson & Ellis Weismer, 2017;Hudry et al, 2010;Kim, Paul, Tager-Flusberg, & Lord, 2014;Luyster, Kadlec, Carter, & Tager-Flusberg, 2008). Correlates of the magnitude of receptive-expressive discrepancy patterns may provide insights into why language development in ASD deviates from typical language development.…”
mentioning
confidence: 99%